2017
DOI: 10.1038/ncomms14961
|View full text |Cite
|
Sign up to set email alerts
|

Large polarization gradients and temperature-stable responses in compositionally-graded ferroelectrics

Abstract: A range of modern applications require large and tunable dielectric, piezoelectric or pyroelectric response of ferroelectrics. Such effects are intimately connected to the nature of polarization and how it responds to externally applied stimuli. Ferroelectric susceptibilities are, in general, strongly temperature dependent, diminishing rapidly as one transitions away from the ferroelectric phase transition (TC). In turn, researchers seek new routes to manipulate polarization to simultaneously enhance susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
5
56
0
2
Order By: Relevance
“…Primarily, this has been achieved by placing a material in the vicinity of a phase transition driven either by chemistry or temperature where most ferroic susceptibilities diverge. More recently, advances in the growth of ferroic thin films has shown that epitaxial strain can be another route by which to manipulate ferroelectric order, ferroic susceptibilities, and domain structures . In turn, there has been extensive work in understanding the role of such ferroelectric/ferroelastic domains and domain walls on the dielectric and piezoelectric response.…”
Section: Thermophysical Properties (At 300 K) Of the Various Thin Filmentioning
confidence: 99%
“…Primarily, this has been achieved by placing a material in the vicinity of a phase transition driven either by chemistry or temperature where most ferroic susceptibilities diverge. More recently, advances in the growth of ferroic thin films has shown that epitaxial strain can be another route by which to manipulate ferroelectric order, ferroic susceptibilities, and domain structures . In turn, there has been extensive work in understanding the role of such ferroelectric/ferroelastic domains and domain walls on the dielectric and piezoelectric response.…”
Section: Thermophysical Properties (At 300 K) Of the Various Thin Filmentioning
confidence: 99%
“…First, we use the Curie temperature (T C ) as an indicator of the influence of our heterostructure design on the ferroelectric properties of the BaTiO 3 membranes, since biaxial strain [25] and strontium content [26,54] are known to strongly affect T C . Using a thermodynamic model [55,56] we can predict the temperature dependence of the ferroelectric polarization for all membrane varieties studied herein (Figure 2a).…”
mentioning
confidence: 99%
“…However, in the last few years HAADF-STEM has emerged as the preferred technique for mapping atomic polar displacements because the samples can be thicker, which helps to preserve the native domain structure, and the interpretation of the image contrast is straightforward and reliable [56,79,115,[132][133][134][135][136][137][138][139]. Mapping of atomic polar displacements from HAADF-STEM images was successfully applied to reveal various domain wall configurations [115,[132][133][134][135]140], flux-closure domain patterns [136], ferroelectric vortex domains [137,138], polarization gradients [56,141], as well as interface and surface reconstructions in ferroelectric thin films [142]; see Figure 16. In these examples, the ferroelectric films present the pseudocubic perovskite-type structure with general formula ABO 3, where A and B are cations of different size and O is the anion bonding to both.…”
Section: Ferroelectric Polarization Mapping From High-resolution Imagesmentioning
confidence: 99%